Analysis of metacognitive characteristics in group discussion on grade 5 fraction materials - Triwahyuningtyas, Dyah; Sa’dijah, Cholis; Muksar, Makbul; Subanji, Subanji (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Math problems require students to think critically in solving a problem. Metacognition leads to the ability to think critically and think at a higher level cognitive process in learning. This study aims to describe the characteristics of metacognition in group discussions on fraction material for grade 5 elementary school students. This type of research uses qualitative descriptive research. The data collection methods used in this research are observation, interview and documentation. The characteristics of students' metacognition can be obtained through observation when students discuss working on problems. Metacognitive activities of 5th grade elementary school students are classified into 3 namely awareness, regulation and evaluation. Students' metacognitive awareness is able to understand the problem and students are able to know what the next thing will be done after understanding the problem. Regulation students are able to choose the strategy that will be used to solve the problem and students are able to apply the chosen strategy to solve the problem. Evaluation students are able to check the answers that are done correctly and are able to ensure that the answers are correct. During group discussions, students are divided into 3 roles, namely students as experts, facilitators and beginners. During group discussion activities to solve problems, not all metacognitive activities appear in each student. Facilitators can influence beginners to be active in the discussion and expert students can help group mates to rethink what they have done before.